2008
DOI: 10.1080/00036840600749839
|View full text |Cite
|
Sign up to set email alerts
|

What makes devout Christians happier? Evidence from Taiwan

Abstract: This study divides the effects of religious involvement on subjective well being (SWB) into direct and indirect channels. The indirect channels mean that, by improving its adherents' present lives, religion enhances their happiness. It is found that devout Christians enhance their SWB by means of one direct channel and three indirect channels; these indirect channels being high health expectations, good family relationship expectations and sound social networks. A good family relationship expectation is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In Ellison (1991), Protestants are found to be happier than Catholics which is explained by the organizational structure of those denominations: Protestants derive greater utility due to a higher autonomy in their belief, due to the collective identity and due to better social integration. Moreover, Christians in general seem to have an advantage compared to other religions in terms of subjective well-being: The probability of being happier is 28% higher for pious Christians than for Buddhists or members of Taiwanese folk religion (Tao 2008). However, there are also studies that do not find any impact of denomination on happiness or life satisfaction in Europe (Hayo, 2007 andGreene andYoon, 2004).…”
Section: Denominationmentioning
confidence: 99%
See 3 more Smart Citations
“…In Ellison (1991), Protestants are found to be happier than Catholics which is explained by the organizational structure of those denominations: Protestants derive greater utility due to a higher autonomy in their belief, due to the collective identity and due to better social integration. Moreover, Christians in general seem to have an advantage compared to other religions in terms of subjective well-being: The probability of being happier is 28% higher for pious Christians than for Buddhists or members of Taiwanese folk religion (Tao 2008). However, there are also studies that do not find any impact of denomination on happiness or life satisfaction in Europe (Hayo, 2007 andGreene andYoon, 2004).…”
Section: Denominationmentioning
confidence: 99%
“…The question of whether, and in what way, religion influences employment, wages or general labor market attainment is the most interesting aspect from the viewpoint of economists. People believing in God may acquire greater human capital, which is rewarded on the labor market (Tao 2008). Furthermore, religious values like modesty, honesty and accuracy tend to increase the quality of daily work and foster collaboration, and thus translates into greater income and better labor market prospects.…”
Section: Income and Labor Market Prospectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, church attendance and religious practices have been noted to improve mental health [4] . In addition, community-based surveys have demonstrated that individuals who attend religious services are happier and more giving of their personal resources [5] . The purpose of this study was to specifically evaluate the impact of patients' depth of religious adherence on their outlook on disease and treatment in a glaucoma population.…”
mentioning
confidence: 99%